Planning and Policy Initiatives for Tourism Development in Nepal: Analysis of Perspectives and Positioning Alignment - Khatiwada, Shreekanta S.; Sharma, Ramji (Journal of Tourism & Adventure, 2025)
The history of tourism in Nepal is cropped up by a gradual sequence from a remote isolated nation till 50s to a vibrant destination of nature, culture and adventure today. The successful ascent of Mt. Annapurna among eight thousanders in 1950 and the world’s tallest peak Mt. Everest in 1953 marked the special milestones in the mountaineering history not only in Nepal but around the globe as well. The government of Nepal has been recognizing tourism as a special catalyst of economic prosperity of the state in continuum since the very first five-year periodic plan of 1956. However, there are inconsistent perspectives and factor of focuses in periodic plans mostly in interpreting the paradigm of tourism, its development pattern and sustainability template. Then again, the growth and development of tourism in most of the destinations of Nepal are ensuing mostly by default rather than planned proceedings. Therefore, all the periodic plans of the Government (1956-2025) were thoroughly reviewed and analyzed for this paper to identify the vision paradigm, growth perspective and the standing alignment of the Government for tourism by using a framework of twelve different factors of focus. The paper concludes with the predicament that the government plans are still muddling through the unclear perspective of sustainability and growth paradigm descending the hazy alignment that is being reflected in the Tourism Master Plan of 1972 and the National Tourism Strategic Plan of 2016 albeit the former suffered from implementing stalemate and the latter is wrecked by the Covid-19 pandemic.